Improved Fodder Cultivation for Sustainable Livestock Management in Bangladesh - Ahmed, Sharif; Debnath, Manik; Miajy, Abdullah; Bhandari, Humnath (International Rice Research Institute, 2024)
Livestock is one of the important sub-sectors of Agriculture in Bangladesh and contributes approximately 1.60% to the GDP. About 20% of the population in the country depends directly on livestock for their livelihoods, while 50% depend on it indirectly. Cattle share the highest relative importance of milk (98%), meat (60%) and hides (60%) production in the country. Despite the huge number of people involved with livestock production, the country suffers from an acute shortage of livestock products such as milk, meat, and eggs. In Bangladesh, the present milk, meat, and eggs production can meet only 50%, 87%, and 63% of the national demand.